2022
DOI: 10.3389/fragi.2021.805126
|View full text |Cite
|
Sign up to set email alerts
|

The Complicated Nature of Somatic mtDNA Mutations in Aging

Abstract: Mitochondria are the main source of energy used to maintain cellular homeostasis. This aspect of mitochondrial biology underlies their putative role in age-associated tissue dysfunction. Proper functioning of the electron transport chain (ETC), which is partially encoded by the extra-nuclear mitochondrial genome (mtDNA), is key to maintaining this energy production. The acquisition of de novo somatic mutations that interrupt the function of the ETC have long been associated with aging and common diseases of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 173 publications
(210 reference statements)
0
20
0
Order By: Relevance
“…Interestingly, mtDNA mutations have been associated with age through increased numbers of mutated mitochondria building up rather than individual mitochondria becoming increasingly damaged. The presence of random mutations even in young healthy individuals supports this hypothesis [ 93 ]. Specific point mutations and deletions in mtDNA are present during early development and even in germline cells [ 90 , 94 ].…”
Section: The Role Of Mtdna In Ageingmentioning
confidence: 88%
“…Interestingly, mtDNA mutations have been associated with age through increased numbers of mutated mitochondria building up rather than individual mitochondria becoming increasingly damaged. The presence of random mutations even in young healthy individuals supports this hypothesis [ 93 ]. Specific point mutations and deletions in mtDNA are present during early development and even in germline cells [ 90 , 94 ].…”
Section: The Role Of Mtdna In Ageingmentioning
confidence: 88%
“…The first described mtDNA deletion, namely the common ∆4977bp mtDNA deletion, accumulates according to age, especially in post-mitotic tissues [ 36 , 37 ]; however, so far, only a few studies have analyzed mtDNA deletion data via a deep sequencing approach by age group [ 11 , 12 ]. These studies also showed an increasing proportion of mtDNA rearrangements with age as well as with carcinogenesis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Premature cellular senescence can be classified by activation of a DNA damage response pathway and its associated signaling kinases which culminate in the stimulation of cell cycle inhibitors, such as p16INK4a, p21/p53, and p27, reduction in cellular proliferation, and loss of Lamin-B activity, which is a marker of the altered enlarged and flattened morphology of senescent cells [ 9 ]. Moreover, the accumulation of mitochondrial DNA (mtDNA), as a result of ROS inducing damage and strand breaks, has been associated with premature onset of ageing in both in vivo and in vitro models, with higher susceptibility to mtDNA mutagenesis [ 10 , 11 ]. Activation of a senescence-associated secretory phenotype (SASP) incorporating a core set of cytokines, such as IL-6, IL-8, IL-13, IGFBPs, and MMPs, results in accumulated senile cells creating a pro-inflammatory microenvironment that indicates establishment of senescence [ 12 ].…”
Section: Introductionmentioning
confidence: 99%